Pengaruh Pemberian Pupuk Organik Bokashi Dan Pupuk Npk Phonska Terhadap Pertumbuhan Dan Produksi Tanaman Jahe Putih Besar (Zingiber officinale) - Ignasius Daung; Suroto Suroto (Universitas Widya Gama Mahakam, 2019)
The purpose of this study was to determine the effect and interaction of Giving Bokashi Organic Fertilizer and NPK Phonska Fertilizer on Growth and Production of Large White Ginger Plants. The study was conducted for 5 months, starting in January 2018 until June 2018 starting from the preparation of planting media, nurseries, planting, to data collection. The location of this study was carried out in the experimental garden Faculty of Agriculture, Widya Gama Mahakam University Samarinda at. K.H. Washid Hasyim. The study was arranged in a 4x3 factorial Randomized Block Design (RBD) and repeated 4 times. The first factor is the Bokashi organic fertilizer (B) consisting of 4 levels, namely: B0 (control), B1 (200 g / polybag), B2 (400 g / polybag), and B3 (600 g / polybag). The second factor is NPK Phonska (P) fertilizer consisting of 3 levels, namely: P0 (control), P1 (30 g / polybag), and P2 (40 g / polybag). The results showed that the treatment of Bokashi organic fertilizer and NPK Phonska fertilizer had a very significant effect on all parameters of observation, while the interaction of the two did not significantly affect all parameters of observation. In general, a dose of 400 g of Bokashi organic fertilizer for growth and production of large white ginger plants produces the best treatment, and a dose of 30 g of NPK Phonska fertilizer for growth and production of large white ginger plants produces the best treatment.